Design of a Comprehensive and innovative ICT-Based Digital Banking Model for Empowering Iran’s Banking Industry - Oloumi Dodaran , Mina; Tabibi, Seyyed Jamaledeen; Zareian, Davoud; Abtahi, Ataollah; Soleimani, Neda (Digital Transformation and Administration Innovation, 2026)
This study aims to create a logical model with well-defined criteria for the effective implementation and execution of digital banking within Iran’s banking sector, using four strategic elements: customer experience, infrastructure, data, and business. A mixed-method research approach (adaptative and factor analysis) was used to develop the model. Descriptive criteria and strategic components from major digital companies such as Microsoft, Capgemini, Oracle, IBM, and a prominent digital bank were identified. These components were compared in a matrix, which led to the formation of the proposed model. The model was validated through observation, interviews, and a questionnaire with 111 questions on a Likert scale, distributed among 528 technology experts. Factor analysis and structural equation modeling, using Smart PLS software, were applied for validation. A comprehensive digital banking model was developed for Iran’s banking industry. The research presents a modular and agile model that addresses market needs, ensures an outstanding digital experience for customers using banking services, and supports open banking by utilizing the latest financial technologies. As customer behavior evolves, Iran’s banking sector is undergoing significant changes in financial interactions. To remain competitive and thrive, banks must embrace digital transformation. This study analyzes current trends in banking and introduces a comprehensive digital banking model that positions the banking ecosystem for digital transformation, laying the foundation for the future of banking.